Analysis of Sport Massage and Personal Trainers New Economic Opportunities - Anam, Khaerul; Muhammad Riyan Hidayatulloh; Lalu Moh Yuda Isnaini; Lalu Mardani Arinaza (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Sport massage and personal trainers are new steps in creating growth opportunities for the Creative Economy, the New Economy that transforms ideas and creates opportunities. The aims of this study are: 1) to determine the relationship between sports massage services and personal trainers to achieve health and fitness goals; 2) To find out what's the economic impact of increasing demand for sports massage services and personal trainers is. 3) To find out How consumer behavior changes when choosing between sports massage and personal training and how this affects the market. 4) To find out the role of sport massagers and personal trainers in driving business growth in the fitness industry. Methods of data analysis using descriptive percentages The sample population in this study was 50 people. The results showed that. 1) The relationship between sports massage services and personal trainers to achieve health and fitness goals 90% answered is very influential. 2) To find out what the economic impact of increasing demand for sports massage services and personal trainers is. 90% answered very impactful. 3) To find out how consumer behavior changes when choosing between sports massage and personal training and how this affects the market. 90% answered very influential. 4) To find out the role of sport massagers and personal trainers in driving business growth in the fitness industry 100% is very encouraging. The conclusion of this study is that 93% of sports massage and personal trainers can create a new economy. The message is that it is hoped that Physical Education students will be increasingly equipped with skills in dealing with opportunities.